Efektivitas Penggunaan Kahoot Terhadap Penguasaan Hiragana Bagi Siswa SMA - VINDA WULANDARI PUTRI; Meira Anggia Putri (Universitas Negeri Padang, 2022)
This study discusses the effectiveness of using Kahoot on Hiragana mastery for high school students. The purpose of this study was to describe the effectiveness of using Kahoot on the mastery of hiragana for high school students. The type of research used is quantitative with quasi-experimental research methods and posttest only control group design research. The population of this research is class XI SMAN 12 Padang who learn Japanese as many as 226 people. As for the sampling, the researchers used class XI IPS 3 and XI IPS 5 at SMAN 12 Padang as many as 78 people. The test instrument is a multiple choice test. Based on the results of data analysis, it was found that the mastery of Hiragana in class XI SMAN 12 Padang using Kahoot media was in very good qualification with an average value of 87.62. While the class without using Kahoot is in good qualification with an average value of 78.22. Based on the results of hypothesis testing, it is concluded that Kahoot is effective because the value of tcount > ttable (2.96 > 1.69).